Significant properties of AA7075-methanol nanofluid flow through diverging channel with porous material: Differential transform method - R.K. Sahoo; S.R. Mishra; Subhajit Panda (Partial Differential Equations in Applied Mathematics)
The recent industrial needs for the production process depending upon heat transfer properties of the fluids. However, the utility of the nanofluid in comparison to the conventional fluid is widely used because of its advanced coolant efficiency. In particular cooling of electronic devices, drug delivery systems, operation theatre, etc. the use of nanofluid shows its influential characteristics. As a result, the contemporary study aims to inspect the heat transmission effects of alloy nanoparticles via the base fluid methanol is presented through a diverging channel. Particularly, the aluminium alloy of AA7075 containing base metal Aluminium (Al) about 87.1–91.4 %, Zinc (Zn) up to 5.1–6.1 %, Magnesium (Mg) about 2.1–2.9 %, Copper (Cu) within the range of 1.2–2.0 %, Chromium (Cr) amounts 0.18–0.28 %, Silicon (Si) usually <0.4 %, Iron (Fe) <0.5 %, Manganese (Mn) up to 0.3 %, and Titanium (Ti) usually <0.2 %. However, the flow through a permeable medium, the interaction of Darcy dissipation energies the flow phenomena. An appropriate similarity transform rule is employed for the transformation of the basic equations and solved analytically via the differential transform method (DTM). Further, a comparative analysis with previously establish outputs is presented to ensure the accuracy of the adopted methodology. The impact of characterizing factors on the flow profiles are presented graphically and the important outcomes are; the velocity profile shows its dual characteristic for the variation of alloy nanoparticles whereas the fluid temperature enhances significantly. Further, heat transport feature enhances for the augmentation in the Eckert number which is exhibited for the inclusion of dissipative heat.